Pengelolaan Aset Tanah Milik Pemerintah Kota Semarang - Krisindarto, Agung (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
In the regional autonomy era, Semarang City’s Administration has put efforts towards independent development financing in its region, one of them through the management cycle of land as a regional asset. The Semarang City Administration is putting it in practice in accordance with the national regulation. However, several problems have started to occur, such as: unclear actual land ownership status and its legal standings, along with low revenue coming from this sector to the regional income. The study uses positivistic-rationalistic approach through descriptive analysis, IPA analysis (Importance-Performance Analysis), and regional financial independence ratio analysis. The study found that Semarang City Administration’s land asset management has several shortcomings, including: management weaknesses, and the absence of asset management optimizing strategy. The study recommends the following, in order to improve the regional finance independence, Semarang City Administration: (1) review of the existing land asset management cycle, and (2) establishment of asset optimizing strategic plan.